Field-of-Study Homogamy - Alena Bičáková; Štěpán Jurajda (Global Labor Organization (GLO), 2017)
This paper reports evidence on the strong tendency of the college educated to match with partners who graduated in the same field of study - a dimension of assortative matching that has been overlooked thus far. We employ Labor Force Survey data covering most EU countries to measure the extent of field-of-study homogamy in prevailing married and cohabiting couples within several years of college graduation. We find that field-of-study homogamy increases almost immediately after graduation to reach very high levels, especially for spouses working in the same industry, and that it varies dramatically across countries. Graduates in Social Sciences display a particularly strong tendency towards homogamy and also have the highest matching theory-implied match gains from homogamous matches.
Keywords: I23; J13; J16; 330; Field-of-Study Homogamy; College Graduates; Marriage and Cohabitation